L’émergence de discours intellectuels islamiques en Allemagne : entre stratégie politique et herméneutique féministe - Jeanette Jouili (Université de Provence, 2008)
The Islamic charter of the Zentralrat der Muslime in Deutschland (ZMD) and female-centred exegetical work undertaken by the Zentrum für Islamische Frauenforschung (ZIF) represent two types of publications stemming from organisations with very divergent profiles and political weight. Both reflect the fundamental problem that Islamic intellectual discourse has to deal with: achieving political recognition of Muslims, on the one side, and competition between different German Islamic associations, on the other. Texts from both sides attempt to articulate Islamic knowledge on ideas of the common good. Two common topics can be discerned: equality between men and women and religious pluralism. The egalitarian vision of the ZIF aspires to a universal framework while remaining imbedded in a particular Islamic tradition. The ideas of the ZMD, conversely, are closely linked to the goal of status recognition within institutional structures while also introducing new theological orientations.